Probing α‐Amino Aldehydes as Weakly Acidic Pronucleophiles: Direct Access to Quaternary α‐Amino Aldehydes by an Enantioselective Michael Addition Catalyzed by Brønsted Bases. Issue 7 (23rd December 2020) - García‐Urricelqui, Ane; de Cózar, Abel; Mielgo, Antonia; Palomo, Claudio
Abstract: The high tendency of α‐amino aldehydes to undergo 1, 2‐additions and their relatively low stability under basic conditions have largely prevented their use as pronucleophiles in the realm of asymmetric catalysis, particularly for the production of quaternary α‐amino aldehydes. Herein, it is demonstrated that the chemistry of α‐amino aldehydes may be expanded beyond these limits by documenting the first direct α‐alkylation of α‐branched α‐amino aldehydes with nitroolefins. The reaction produces densely functionalized products bearing up to two, quaternary and tertiary, vicinal stereocenters with high diastereo‐ and enantioselectivity. DFT modeling leads to the proposal that intramolecular hydrogen bonding between the NH group and the carbonyl oxygen atom in the starting α‐amino aldehyde is key for reaction stereocontrol. Abstract : Harnessing limitations : The ease with which α‐amino aldehydes racemize is the starting point for their utilization beyond the limits of their essentially exclusive use as electrophiles, as exemplified in the reaction of N‐alkoxycarbonyl α‐amino aldehydes with nitroolefins. This reaction is assisted by a weak bifunctional Brønsted base to give quaternary α‐amino aldehydes with an adjacent ternary stereogenic center.